Diabetes Mellitus in Children and Adolescents with Genetic Syndromes - Schmidt, F.; Kapellen, T. M.; Wiegand, S.; Herbst, A.; Wolf, J.; Fröhlich-Reiterer, E. E.; Rabl, W.; Rohrer, T.; Holl, R. W.; null (Experimental and Clinical Endocrinology & Diabetes, 2012)
Several genetic syndromes are associated with diabetes mellitus (DM). This study aimed to analyse data from the DPV database with regard to frequency, treatment strategies and long-term complications in paediatric DM patients with genetic syndromes, including Turner syndrome (TS), Prader-Willi syndrome (PWS), Friedreich ataxia (FA), Alström syndrome (AS), Klinefelter syndrome (KS), Bardet-Biedl syndrome (BBS), Berardinelli-Seip syndrome (BSS) and Down syndrome (DS).Longitudinal data for 43 521 patients with DM onset at age <20 years were collected from 309 treatment centres in Germany and Austria using the DPV software. Data included anthropometric parameters, type of diabetes, mean age, age at diabetes onset, daily insulin dose, HbA1c, micro- and macroalbuminuria, retinopathy and dyslipidaemia. Descriptive statistics and standard statistical tests were used for data analysis.In total, 205 DM patients had one of the following syndromes: DS (141 patients), TS (24), PWS (23), FA (5), AS (5), KS (4), BBS (2) and BSS (1). Diabetes-specific antibodies were positive in the majority of patients with DS, TS and FA.Despite the well-known association between DM and certain syndromic disorders, the number of affected patients in the German and Austrian paediatric diabetic population is very low. Nevertheless, physicians should be aware of syndromic forms of diabetes. Joint multicentre analyses are needed to draw relevant conclusions.
Keywords: Turner syndrome; Prader-Willi syndrome; Friedreich ataxia; Alström syndrome; Klinefelter syndrome; Pediatric diabetology